Mineral effects on chemical and physical transformations of fast pyrolysis products of cellulose-based model fuels in N2 and CO2. (15th May 2023) - Eckhard, Till; Pflieger, Christin; Russo, Carmela; Freisewinkel, Erik; Eisenbach, Tim; Böttger, Jannik; Senneca, Osvalda; Apicella, Barbara; Schiemann, Martin; Span, Roland; Scherer, Viktor; Muhler, Martin; et al.
Highlights: Role of AAEM in catalyzing pyrolysis reactions in N2 and CO2. Minerals catalyze solid, liquid, and gaseous pyrolysis products. Mineral doping, heating rate, temperature, and atmosphere all influenced the pyrolysis products. Minerals catalytically affected the decomposition of the levoglucosan fraction in the tars. CO2 inhibited (700 °C) or enhanced (1027 °C) the formation of polycyclic aromatic hydrocarbon. Abstract: This paper investigates the changes in reactivity and physicochemical characteristics of char and tar produced from severe heat treatment in either inert or CO2 -rich atmospheres of a synthetic fuel doped with Fe&Mg and K&Mg sulfates. The mineral-free model fuel was obtained by hydrothermal carbonization (HTC) of cellulose. The comparison of Py-GC/MS-GC/TCD, heated strip reactor (HSR), and drop tube reactor (DTR) results highlighted that mineral doping, heating rate, temperature, residence time and atmosphere all interacted and influenced the pyrolysis products. Fe&Mg increased the light permanent gases during flash pyrolysis. The minerals catalytically affected the decomposition of the levoglucosan fraction in the tars. In N2, the addition of K&Mg influenced the oxy-aliphatic tars, while Fe&Mg had a stronger impact on oxy-aromatic compounds. Depending on the pyrolysis temperature and residence time (and reactor type), CO2 inhibited (700 °C in the HSR) or enhanced (1027 °C in the DTR) the formation of polycyclic aromatic hydrocarbon (PAHs) in the tars. Chars doped with Fe&Mg always exhibited higher reactivity than the chars doped with K&Mg. While the presence of CO2 during pyrolysis favored the aromatization of the chars especially in combination with doped minerals, alkali mineral interaction with CO2 decisively altered char reactivity.